Pressureless Sintering of Hafnium Carbide–Silicon Carbide Ceramics. Issue 6 (19th April 2013) - Liu, Ji‐Xuan; Huang, Xiao; Zhang, Guo‐Jun; Parthasarathy, T.
<x xml:space="preserve">Abstract</x> HfC‐30 vol%SiC ceramics with a relative density of 99.7% was obtained by pressureless sintering at 2300°C for 0.5 h. The resultant ceramics showed fine microstructure with HfC grain size around 1 μm. The hardness (20.5 ± 0.2 GPa), bending strength (396 ± 56 MPa), and fracture toughness (2.81 ± 0.18 MPa·m1/2) of HfC‐30 vol%SiC ceramics were at least 20% higher than those of monolithic HfC ceramics. The influences of SiC particle size, volume fraction, and the oxide impurity on the microstructure evolution of HfC‐based ceramics were examined. The results indicate that SiC addition and the oxygen impurity introduced by ball milling play opposite roles in the HfC grain growth during sintering. The oxide impurity introduced by ball milling caused the HfC grain coarsening, whereas SiC particles inhibited the grain growth of HfC significantly.